IMPROVING THE ACTIVATION MODEL OF SYNONYMS IN PRIMARY SCHOOL STUDENTS' SPEECH (Scientific journal of the Fergana State University, 2024)
This article analyzes the process of improving the model of the activation of meaningful words in the speech of students of junior school age. Students' lack of vocabulary, lack of knowledge of the dictionary meaning of a word in their mother tongue, and lack of concepts about a series of words with the same meaning cause problems like the above. Taking into account that this period is the main stage for students to form a linguistic personality and learn to communicate with others from the primary education age, it is believed that it is necessary to pay attention to increasing the vocabulary of primary school students and teaching them to distinguish the meanings of words from this period. . Selection of practical methods of teaching specific to mother tongue education and improvement of competencies that meet the requirements for their application in the educational process. From this point of view, the technological approach to the teaching of the mother tongue and the technologicalization of education and the assessment of its unique result are important for this process. The model for improving the methodical system of activating meaningful words in the speech of elementary school students is integrated and open, and scientific views and conclusions are given about the purposeful development of improving the methodology of activating meaningful words in the speech of elementary school students and the compatibility of the set goal with the result.